“The Best Risky Point”: Agency and Decision-Making in Young Unaccompanied Asylum Seekers' Stories of Leaving Home and Travelling to Australia - Stratford, Tori; Nethery, Amy; Mansouri, Fethi (Refuge, 2023)
Seeking asylum is a perilous endeavour with unpredictable border crossings, protection prospects, and settlement outcomes. Young unaccompanied asylum seekers face even greater risks. Yet exclusively characterizing them as vulnerable or passive ignores their agency in making choices in a range of unique, dynamic, and challenging circumstances. In this article, we use deep ethnographic methodology to amplify young asylum seekers’ voices, examining their capacity to enact agency along the asylum journey. We employ Bourdieu’s non-doxic contexts and Jackson’s “border situations” to describe the unstable environments young people navigate at home and during their journey to Australia.Our findings reveal a nuanced picture of young people both as objects of other people’s decisions (with reduced agency) and as highly engaged in dynamic decision-making during their journey to Australia (with more salient agency). These findings indicate the importance of research methods that steer away from fixed assumptions around vulnerability and victimhood to recognize the agentic capacity of young people to make life-defining decisions even as they find themselves in transnational border situations that seek to control and constrain them.